The Implementation of Tangible Interaction in Microcontroller-Based Interactive Animal Introduction Game â€œMARGAâ€ for Intellectual Disability Children - Rio Korio Utoro; Putri Ilyassani; Benedicta Butarbutar; Fathari Zain Hardianto; M. Fauzi Usda (IJAIT (International Journal of Applied Information Technology), 2023)
According to the interview results with the headmaster of Autism Pelita Hafidzh Bandung Special School, children with intellectual disabilities have learning limitations, including difficulty remembering, quickly forgetting, being distracted, having little interest, and IQ below the average of normal children. Therefore, the innovation of the MARGA game, an acronym for Multimedia Embedded Rig for Guided Assistant, was created using tangible interaction to assist these children in learning about animals. Technical testing was conducted twice, namely testing the suitability of tags and the speed of tag reading time, resulting in an average speed of reading RFID tags of 2,653 seconds. In addition to conducting beta testing on two children with intellectual disabilities at Autism Pelita Hafidzh Bandung Special School. Research shows that children with intellectual disabilities who have tried playing MARGA reach the learning target set by Autism Pelita Hafidzh Bandung Special School more quickly.